2007
DOI: 10.1038/ismej.2007.80
|View full text |Cite
|
Sign up to set email alerts
|

Modeled contributions of three types of diazotrophs to nitrogen fixation at Station ALOHA

Abstract: A diagnostic model based on biomass and growth was used to assess the relative contributions of filamentous nonheterocystous Trichodesmium and unicellular cyanobacteria, termed Groups A and B, to nitrogen fixation at the North Pacific Station ALOHA over a 2-year period. Average (and 95% confidence interval, CI) annual rates of modeled monthly values for Trichodesmium, Group B and Group A were 92 (52), 14 (4) and 12 (8) mmol N per m 2 per year, respectively. The fractional contribution to modeled instantaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 62 publications
(76 reference statements)
1
47
0
Order By: Relevance
“…For instance, nonoxygenic diazotrophs (e.g., Candidatus Atelocyanobacterium thalassa; Thompson et al 2012) do not fix CO 2 , and the primary benefit of high P CO 2 seems to be associated CO 2 fixation, whereas N 2 fixation likely receives secondary benefits (Law et al 2012). Thus, assuming that oceanic P CO 2 will increase within the next 100 yr, N 2 fixation by unicellular oxygenic diazotrophs will likely be affected by future concentrations of P CO 2 , mostly in areas where they reach high densities, which are known to include tropical regions of the Atlantic Ocean (Langlois et al 2008) and parts of the Pacific Ocean near northern Australia and Hawaii (Montoya et al 2004;Church et al 2005;Goebel et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, nonoxygenic diazotrophs (e.g., Candidatus Atelocyanobacterium thalassa; Thompson et al 2012) do not fix CO 2 , and the primary benefit of high P CO 2 seems to be associated CO 2 fixation, whereas N 2 fixation likely receives secondary benefits (Law et al 2012). Thus, assuming that oceanic P CO 2 will increase within the next 100 yr, N 2 fixation by unicellular oxygenic diazotrophs will likely be affected by future concentrations of P CO 2 , mostly in areas where they reach high densities, which are known to include tropical regions of the Atlantic Ocean (Langlois et al 2008) and parts of the Pacific Ocean near northern Australia and Hawaii (Montoya et al 2004;Church et al 2005;Goebel et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The Baltic Sea is among the world's largest brackish seas and regularly experiences extensive blooms of diazotrophic heterocystous cyanobacteria (Stal et al, 2003) providing N-input almost as large as the riverine load (Larsson et al, 2001). Cyanobacterial N 2 fixation is also significant in open oceans (Goebel et al, 2007), but molecular techniques targeting the nifH gene of the nitrogenase enzyme have revealed that heterotrophic diazotrophs are also present and nifH transcribed in diverse marine and estuarine environments (reviewed in Riemann et al, 2010). However, their significance to N 2 fixation and the factors controlling their activity and distribution patterns are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, unicellular diazotrophic cyanobacteria, named group A (UCYN-A), group B (UCYN-B) and group C (UCYN-C), have been discovered on the basis of molecular techniques (Zehr et al 2001, Langlois et al 2005, Foster et al 2007, and their contribution to total nitrogen fixation was estimated to be equal to, or even greater than, that of Trichodesmium spp. (Falcón et al 2004, Goebel et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, unicellular diazotrophic cyanobacteria, named group A (UCYN-A), group B (UCYN-B) and group C (UCYN-C), have been discovered on the basis of molecular techniques (Zehr et al 2001, Langlois et al 2005, Foster et al 2007, and their contribution to total nitrogen fixation was estimated to be equal to, or even greater than, that of Trichodesmium spp. (Falcón et al 2004, Goebel et al 2007.Although most cyanobacterial diazotrophic groups can be detected simultaneously in the marine environment (Church et al 2005a, Foster et al 2007, Fong et al 2008, different diazotrophic groups have shown different patterns of distribution in the ocean (Riemann et al 2010). Trichodesmium spp.…”
mentioning
confidence: 99%